The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/asi.20000
|View full text |Cite
|
Sign up to set email alerts
|

From two‐step flow to the Internet: The changing array of sources for genetics information seeking

Abstract: The diffusion of the Internet has radically expanded the readily available sources for information of all types. Information that was once obtained second-hand from friends and acquaintances-the traditional "two-step flow"-is now found easily through the Internet. The authors make use of survey data to explore this thesis in regards to information sources about genetic testing and the influence of the Internet on the information seeking behaviors of the public. A telephone survey of a random sample of 882 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 50 publications
3
69
1
2
Order By: Relevance
“…The subjects were asked to place their sources in three zones, (1) most significant sources, (2) intermediate sources, and (3) peripheral sources, and to illustrate the different uses of the information sources in each zone. In contrast to the results shown in the previous study by Case et al (2004), it was found that people still preferred to use human resources in general, followed by print media materials like newspapers and books, and network sources. Savolainen (2007) examined the source preferences of environmental activists with the modified framework of an "information source horizon," and the result was almost the same as his previous study.…”
Section: Source Preferencescontrasting
confidence: 99%
See 2 more Smart Citations
“…The subjects were asked to place their sources in three zones, (1) most significant sources, (2) intermediate sources, and (3) peripheral sources, and to illustrate the different uses of the information sources in each zone. In contrast to the results shown in the previous study by Case et al (2004), it was found that people still preferred to use human resources in general, followed by print media materials like newspapers and books, and network sources. Savolainen (2007) examined the source preferences of environmental activists with the modified framework of an "information source horizon," and the result was almost the same as his previous study.…”
Section: Source Preferencescontrasting
confidence: 99%
“…It was observed that the information sources which had been traditionally popular, such as people, newspapers, magazines, and television, have been gradually replaced by Internet sources (Kaye and Johnson, 2003;Hektor, 2003). Interestingly, Case et al (2004) found that the Internet was the most preferred source among people looking for information about genetics and diseases and constituted 45% of the first choice sources, followed by medical doctors (18.4%), a public library (14.1%), family members (10.6%), medical sources (8.7%) and mass media sources other than the Internet (1%). Mass media sources and sources labeled friends were identified as less usable sources in this study.…”
Section: Source Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical-genetics patients and parents of children with suspected genetic conditions report using the Internet to self-diagnose, to find specialists, and to increase their genetic literacy or acquire medical vocabulary [51][52][53]. In fact, patients may rely more heavily on the Internet as a source of genetics information than they do on health professionals [54]. Genetics patients report dissatisfaction with the information provided by health professionals as one of their motivations for accessing online information [52,55,56].…”
Section: Influence Of the Internet As A Common Source Of Informationmentioning
confidence: 99%
“…Even though the internet serves as the primary source for gathering genetic information [44], participants could have sought information through other websites, other media channels, or interpersonal communication with healthcare providers, family, or friends. These forms of genetic information seeking are not reflected in these data.…”
Section: Discussionmentioning
confidence: 99%